Effects of Pickleball Intervention on the Self-Esteem and Symptoms of Patients with Schizophrenia - Tsai-Chieh Chien; Chao-Chien Chen (Sports)
Background: Schizophrenia is classified by the World Health Organization (WHO) as one of the top ten diseases contributing to the global medical economic burden. Some studies have pointed out that exercise is effective for physical and mental health, as well as cognition. We hypothesized that participation in pickleball intervention would lead to improved self-esteem and reduced psychiatric symptoms in schizophrenia patients. Method: We recruited participants with schizophrenia from a long-term care facility and a regional hospital, dividing them into two groups based on the institutions. The experimental group underwent a nine-week pickleball exercise intervention, with sessions three times a week, each lasting 90 min, and a Dink ball test was conducted weekly. Questionnaires on self-esteem and the short-form health survey were collected both before and after the intervention. Result: This trial included 30 patients, divided equally into the experimental group (n = 15) and the control group (n = 15). After the nine-week pickleball intervention, there were no significant differences between the experimental and control groups in the Rosenberg Self-Esteem Scale (RSES) (p = 0.153) or the Brief Symptom Rating Scale (BSRS-5) (p = 0.289). However, the Dink test scores in the experimental group showed significant improvements in physical activity capabilities and attention over time, with average hit counts increasing from 5.3 ± 1.5 to 10.7 ± 2.3 (p < 0.01). Conclusions: Although the pickleball intervention did not yield significant differences in self-esteem and symptom measures between groups, the improvements observed in physical performance and attention in the experimental group suggest that exercise remains a feasible complementary approach for managing schizophrenia symptoms. Further research with larger sample sizes is recommended.